Brazeability and mechanical properties of Ag-Cu-Sn brazing filler metals on copper-brazed joint - Basri, D.K.; Sisamouth, L.; Farazila, Y.; Miyazawa, Y.; Ariga, T. (Maney Publishing, 2014)
This paper describes an investigation of cadmium-free silver brazing filler metals, the ternary Ag-Cu-Sn alloys. The influences of tin content on solidus and liquidus temperatures and gap filling ability of Ag-Cu-Sn alloys on copper were investigated. Microstructures of the joint and the shear strength were examined. Investigation on gap filling ability test procedure was performed according to ISO 5179-1983. The result from differential thermal analysis showed that the solidus and liquidus temperatures of the filler metals decreased with the increment of tin content in Ag-Cu-Sn. The results from the shear test showed that the brazed joint exhibited the highest strength at 10 wt-% tin content in the filler metal. The joint gaps of less than 0.10 mm were proposed when designing the brazed joint for Ag-Cu-Sn filler metals.